2013
DOI: 10.1007/s11427-013-4503-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of acute kidney injury by noninvasive arterial spin labeling perfusion MRI: a pilot study

Abstract: The kidneys are essential for maintaining homeostasis, are responsible for the reabsorption of water, glucose and amino acids, and filter the blood by removing waste. Acute kidney injury (AKI) is a syndrome characterized by the rapid loss of renal excretory function and the accumulation of end metabolic products of urea and creatinine. AKI is associated with the later development of chronic kidney disease and end-stage kidney disease, and may eventually be fatal. Early diagnosis of AKI and assessments of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…The results showed that the cortical values for TIs 1800 msec and 2000 msec were statistically similar, in both the control and CKD groups. In previous studies, various TIs have been used for renal ASL in humans, including 900 msec, 1200 msec, 1400 msec, 1500 msec, and 2000 msec . To choose the optimal TIs for the 3D ASL sequence we used in this study, a preliminary test was performed to compare the TIs ranging from 1200 to 2000 msec in a small group of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the cortical values for TIs 1800 msec and 2000 msec were statistically similar, in both the control and CKD groups. In previous studies, various TIs have been used for renal ASL in humans, including 900 msec, 1200 msec, 1400 msec, 1500 msec, and 2000 msec . To choose the optimal TIs for the 3D ASL sequence we used in this study, a preliminary test was performed to compare the TIs ranging from 1200 to 2000 msec in a small group of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in perfusion measurements as a biomarker for assessing renal function and for characterizing renal masses. Quantitative perfusion is reduced in renal insufficiency and in hemodynamically significant renal artery stenosis (710). In renal cell carcinoma (RCC), perfusion has proven value because of the relationship between angiogenesis, prognosis, and response to different targeted therapies in these tumours (1117).…”
Section: Introductionmentioning
confidence: 99%
“…ASL has been successfully applied to imaging perfusion in organs and lesions in the abdomen (8,1013,15,16,2640). Initial studies have focused on single-slice two-dimensional (2D) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models, it distinguishes the evolution from moderate to severe AKI, with subsequent restoration of normal pH values serving as an indicator for renal recovery . Arterial spin labeling perfusion MRI also accurately assesses cortical and medullary malperfusion in the setting of AKI, but the relationship between arterial spin labeling measurements and renal recovery could not be quantified . Further studies in humans will be needed to fully assess the sensitivity and specificity of imaging to provide timely, noninvasive information regarding AKI progression and recovery.…”
Section: Cut‐off Criteria Used In Clinical Trialsmentioning
confidence: 99%